Inter‐laboratory trial of a standardized sediment contact test with the aquatic plant Myriophyllum aquaticum (ISO 16191). (24th January 2014) - Feiler, Ute; Ratte, Monika; Arts, Gertie; Bazin, Christine; Brauer, Frank; Casado, Carmen; Dören, Laszlo; Eklund, Britta; Gilberg, Daniel; Grote, Matthias; Gonsior, Guido; Hafner, Christoph; et al.
Abstract A whole‐sediment toxicity test with Myriophyllum aquaticum has been developed by the German Federal Institute of Hydrology and standardized within the International Organization for Standardization (ISO; ISO 16191). An international ring‐test was performed to evaluate the precision of the test method. Four sediments (artificial, natural) were tested. Test duration was 10 d, and test endpoint was inhibition of growth rate (r) based on fresh weight data. Eighteen of 21 laboratories met the validity criterion of r ≥ 0.09 d−1 in the control. Results from 4 tests that did not conform to test‐performance criteria were excluded from statistical evaluation. The inter‐laboratory variability of growth rates (20.6%–25.0%) and inhibition (26.6%–39.9%) was comparable with the variability of other standardized bioassays. The mean test‐internal variability of the controls was low (7% [control], 9.7% [solvent control]), yielding a high discriminatory power of the given test design (median minimum detectable differences [MDD] 13% to 15%). To ensure these MDDs, an additional validity criterion of CV ≤ 15% of the growth rate in the controls was recommended. As a positive control, 90 mg 3, 5‐dichlorophenol/kg sediment dry mass was tested. The range of the expected growth inhibition was proposed to be 35 ± 15%. The ring test results demonstrated the reliability of the ISO 16191 toxicity test and its suitability as a tool to assess the toxicity of sediment and dredged material. Environ Toxicol Chem 2014;33:662–670. © 2013 SETAC